Derek Jarman’s allegories of spectacle: inter-artistic embodiment - Chinita, Fátima (2015)
ABSTRACT - Derek Jarman was a multifaceted artist whose intermedial versatility reinforces a strong authorial discourse. He constructs an immersive allegorical world of hybrid art where different layers of cinematic, theatrical and painterly materials come together to convey a lyrical form and express a powerful ideological message. In Caravaggio (1986) and Edward II (1991), Jarman approaches two european historical figures from two different but concomitant perspectives. In Caravaggio, through the use of tableaux of abstract meaning and by focusing on the detailing of the models’ poses, Jarman re-enacts the allegorical spirit of Caravaggio’s paintings through entirely cinematic resources. Edward II was a king, and as a statesman he possessed a certain dose of showmanship. In this film Jarman reconstructs the theatrical basis of Christopher Marlowe’s Elizabethan play bringing it up to date in a successfully abstract approach to the musical stage. In this article, I intend to conjoin the practice of allegory in film with certain notions of existential phenomenology as advocated by Vivian Sobchack and Laura U. Marks, in order to address the relationship between the corporeality of the film and the lived bodies of the spectators. In this context, the allegory is a means to convey intradiegetically the sense-ability at play in the cinematic experience, reinforcing the textural and sensual nature of both film and viewer, which, in turn, is also materially enhanced in the film proper, touching the spectator in a supplementary fashion. The two corporealities favour an inter-artistic immersion achieved through coenaesthesia.